2011
DOI: 10.3892/ol.2011.307
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor and T-regulatory functions of Foxp3 are mediated through separate signaling pathways

Abstract: Abstract. Foxp3 is a nuclear transcription factor that is both a tumor suppressor factor and regulator of T-regulatory cell (Treg) function, and is a potential therapeutic target in both autoimmunity and cancer. In order to distinguish molecular pathways responsible for these separate Foxp3 functions, deletion mutants of Foxp3 proteins were transduced and analyzed for cytotoxic activity in human cancer cell lines Skov3, MDA-MB-231, MCF-7 and Jurkat. Human Foxp3 cDNA mutants were amplified and ligated to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have shown that there is subpopulation of T cells called regulatory cells (Tregs) responsible for the strength and scope regulation of the immune system response. Numerous studies have demonstrated that an increased Tregs subpopulation percentage reduces the sensitivity of the immune system to external or changed in the disease process antigens, which allows the growth of tumors [21,22]. On the other hand decreased Tregs percentage increases the strength of immune response, which may lead to chronic inflammatory diseases and autoimmune diseases [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that there is subpopulation of T cells called regulatory cells (Tregs) responsible for the strength and scope regulation of the immune system response. Numerous studies have demonstrated that an increased Tregs subpopulation percentage reduces the sensitivity of the immune system to external or changed in the disease process antigens, which allows the growth of tumors [21,22]. On the other hand decreased Tregs percentage increases the strength of immune response, which may lead to chronic inflammatory diseases and autoimmune diseases [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 has various distinguishable functional domains: (i) an N-terminal domain (from a.a. 1 to 193) responsible for transcriptional repression, (ii) a zinc finger (a.a. 200–223), a leucine-zipper (LZ)-like motif (a.a. 240–261), which facilitates the formation of FOXP3 homo-dimers or tetramers, and (iii) the highly conserved carboxy terminal forkhead domain (FKH; from a.a. 338 to 421) responsible for the DNA binding [ 30 ]. It has been described that the tumor suppressor activity of FOXP3 is located in the N-terminal region of the protein (Aa 1-196) [ 31 ]. In a recent work, Gong et al have shown that the ectopic expression of FOXP3 inhibited hepatocarcinoma cell line (HCC) proliferation, migration, and invasion, while FOXP3 downregulation promoted HCC growth [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been described that this tumor suppressor activity is located in the N-terminal region of Foxp3, since a C-truncated versions of the protein do not retain this property (54). The authors described that this activity was independent of NFAT-FOXP3 interaction which is located in the FKH region of FOXP3 (55).…”
Section: The Structure/function Analysis Of Foxp3mentioning
confidence: 99%
“…As mentioned above, FOXP3 expression is not restricted to the lymphocyte lineage but it is also present in cancer cells, especially in breast cancer cells, where it has been demonstrated to be a cancer suppressor gene and an important regulator of the HER2/ErbB2 and SKP2 oncogenes ( 27 , 30 ). It has been described that this tumor suppressor activity is located in the N-terminal region of Foxp3, since a C-truncated versions of the protein do not retain this property ( 54 ). The authors described that this activity was independent of NFAT-FOXP3 interaction which is located in the FKH region of FOXP3 ( 55 ).…”
Section: The Structure/function Analysis Of Foxp3mentioning
confidence: 99%